KODE ETIK GURU DAN DAMPAKNYA TERHADAP MOTIVASI BELAJAR SISWA DI ERA KURIKULUM MERDEKA - Hafidz Al Faqih; M. Wildan Ahfadh; Fadhilatul Fauziah; Nur Khasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The teacher's code of ethics is a set of norms and values that serves as a guide for teachers' professional conduct. This study aims to analyze the impact of the implementation of the teacher's code of ethics on student learning motivation in the Merdeka Curriculum era through a literature review approach. The method used is a literature study by examining various academic sources including books, scientific journals, and relevant education policy documents. The findings indicate that the teacher's code of ethics, particularly in the dimensions of honesty, fair assessment, and respect for student uniqueness, is closely related to the development of students' intrinsic motivation. Gaps between ethical values that teachers are expected to uphold and actual classroom practices potentially create a learning climate that is not conducive to student development. This study also finds that the Merdeka Curriculum provides broader space while simultaneously demanding a deeper understanding of professional ethics from every teacher. Therefore, strengthening the teacher's code of ethics needs to be explicitly integrated into teacher professional development programs, particularly in the context of implementing the Merdeka Curriculum at the secondary education level.